INTEGRASI CODING DAN REALISTIC MATHEMATICS EDUCATION BERBASIS BUDAYA ACEH UNTUK MENUMBUHKAN KREATIVITAS MATEMATIS SISWA SD - Rahmi Hayati; Rohantizani; Nuraina; Asrul Karim; Fachrurazi; Marzuki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the integration of coding and Acehnese culture-based Realistic Mathematics Education (RME) in elementary school mathematics learning, analyze the learning process that supports the development of students' mathematical creativity, and identify local cultural values ​​that can be adapted in technology-based and realistic learning designs. This study uses a descriptive qualitative approach with an exploratory study design. The research subjects included teachers and students in grades IV–V at an elementary school in Bireuen Regency, Aceh. Data were obtained through observation, interviews, and documentation, then analyzed interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the integration of coding and Acehnese culture-based RME can create meaningful, creative, and contextual mathematics learning. The application of local cultural contexts such as Acehnese rumoh motifs and Acehnese cultural values ​​helps students understand mathematical concepts concretely and closely related to their lives. Meanwhile, the application of coding through platforms such as Scratch and Blockly fosters logical and systematic thinking skills and increases creativity in problem-solving. Collaborative and reflective learning reinforces the values ​​of meuseuraya (cooperation) and tameh (politeness), so that students develop not only cognitively but also socially and emotionally. This study concludes that the synergy between local culture, digital technology, and a realistic approach is an effective strategy for realizing meaningful 21st-century mathematics learning rooted in cultural identity. This model can be used as a reference for teachers, schools, and researchers to develop learning innovations based on local wisdom in the digital era.